Global Environmental Warfare - Herndon, J. Marvin; Whiteside, Mark (Advances in Social Sciences Research Journal, 2020)
Unlike traditional forms of warfare that cause environmental harm as collateral damage, today vast segments of biota-populations, including humans, are at risk from undeclared global environmental warfare, undertaken through deception and deceit, orchestrated by undisclosed perpetrators for undisclosed purposes. As we reveal here, the purported goal of preventing environmental warfare was the key to developing a means to co-opt sovereign nations into waging covert, highly destructive environmental warfare against their own citizens. The means involved deceiving leaders of sovereign nations into signing onto a deceptively-worded “Trojan horse” international treaty ostensibly to prohibit environmental warfare, but which specifically does not prohibit “peaceful” environmental modification where “environmental modification techniques” refers to any technique for changing – through the deliberate manipulation of natural processes – the dynamics, composition or structure of the Earth, including its biota, lithosphere, hydrosphere and atmosphere, or of outer space.” Moreover, that international treaty mandates contribution and co-operation in unspecified environmental modification, by unspecified entities, without specificity of risks to human and environmental health. Although “environmental modification techniques” are applied and conducted with secrecy and deception, the horrific environmental damage, ascertained by scientific forensic investigations and reviewed here, cannot possibly be considered “peaceful” but instead constitute global environmental warfare. Citizens everywhere must wake up, look up, speak up, and demand an end to this environmental warfare.